Practical and scalable preparation of Minodronic acid and Zolpidem from 2-chloroimidazole[1, 2-a]pyridines. Issue 8 (22nd February 2019) - Wang, Yuheng; Zhang, Bingbing; Zheng, Yinying; Ma, Qiaoning; Sui, Qiang; Lei, Xinsheng
Abstract: Practical and scalable procedures for Minodronic acid and Zolpidem are developed with short reaction sequences from 2-aminopyridines and maleic anhydride, respectively. The new procedures avoid column chromatography for the purification in all synthetic steps. Key aspects of this development involve reductive hydrodechlorination and Suzuki coupling reaction of 2-chloroimidazole[1, 2- a ]pyridines, and their application towards synthesis of the two drugs is also addressed. Graphical abstract: Image 1